Analisis Kualitas Internet Financial Reporting Pada Perusahaan Consumer di Indonesia - Budiyanti, Harti; Nugroho, Affan Kautsar (Owner : Riset dan Jurnal Akuntansi, 2024)
Companies in Indonesia are currently obligated to provide annual reports on its websites. The annual report presented on companies’ website becomes the information sources for its stakeholders.This research aims to understand the quality of financial reporting internet of consumer companies listed in Indonesia Stock Exchange. This research uses financial reporting internet index which consists of four components namely content, timeliness, technology, and user support to assess the quality of financial reporting internet.The analysis method of this research is descriptive analysis. The result of this research shows that consumer companies in Indonesia disclose annual reports on their websites and have good user support. While the timeliness index and technology of other consumer companies in Indonesia are not quite good